1998
DOI: 10.1093/ajcn/68.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Role of cobalamin intake and atrophic gastritis in mild cobalamin deficiency in older Dutch subjects

Abstract: Background:The reason for the high prevalence of mild cobalamin (vitamin B-12) deficiency in the elderly is poorly understood. Objective: We aimed to determine the reason for this high prevalence. Design: We examined cobalamin intake, the presence and severity of atrophic gastritis, the presence of Helicobacter pylori infection, and plasma cobalamin and methylmalonic acid (MMA) concentrations in 105 healthy, free-living, older subjects aged 74-80 y. Results: Mild cobalamin deficiency, ie, low to low-normal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(116 citation statements)
references
References 46 publications
4
109
0
3
Order By: Relevance
“…Different prevalence rates of atrophic gastritis could reflect different rates of Helicobacter pylori infection in the various populations surveyed because H. pylori causes chronic gastritis and can lead to atrophic gastritis (Fennerty, 1994). However, the prevalence of H. pylori in a group of older New Zealanders (B50%) (Collett et al, 1999) is similar to that reported in studies carried out in the US (Everhart et al, 2000) and The Netherlands (van Asselt et al, 1998). Although atrophic gastritis was strongly associated with low serum vitamin B 12 in our study population, 77% of people with deficient (o148 pmol/l) and 94% with marginal vitamin B 12 (148-221 pmol/l) were classifed as having normal mucosa or superficial gastritis.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Different prevalence rates of atrophic gastritis could reflect different rates of Helicobacter pylori infection in the various populations surveyed because H. pylori causes chronic gastritis and can lead to atrophic gastritis (Fennerty, 1994). However, the prevalence of H. pylori in a group of older New Zealanders (B50%) (Collett et al, 1999) is similar to that reported in studies carried out in the US (Everhart et al, 2000) and The Netherlands (van Asselt et al, 1998). Although atrophic gastritis was strongly associated with low serum vitamin B 12 in our study population, 77% of people with deficient (o148 pmol/l) and 94% with marginal vitamin B 12 (148-221 pmol/l) were classifed as having normal mucosa or superficial gastritis.…”
Section: Discussionmentioning
confidence: 51%
“…In 248 Kansas residents (465 y), the prevalence of atrophic gastritis was 9%; 5% had severe atrophic gastritis (Hurwitz et al, 1997). In 108 Dutch seniors (74-80 y), the prevalence of atrophic gastritis was 32% and 13% had severe atrophic gastritis using stricter criteria (PG I/II o1.6 and PG I o17) (van Asselt et al, 1998). In Finland, a 5-6% prevalence of severe atrophic gastritis was found in 425 older residents (460 y) using biopsies and a less stringent cut point of PG I o25 mg/l (Varis et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 of the present study indicate that some elderly respondents with raised MMA levels also have abnormal plasma urea and creatinine concentration, and therefore impaired kidney function. Many other studies have also detected a link between raised blood MMA levels and impaired kidney function (Stabler et al, 1986;Rasmussen et al, 1990a, b;Joosten et al, 1993;Lindenbaum et al, 1994;Koehler et al, 1996;Norman, 1998Norman, , 1999van Asselt et al, 1998;Herrmann et al, 2000;Hvas et al, 2000). According to Whitehead et al (1994), the 97.5th centile of plasma creatinine in adults aged 25 -55 y is approximately 122 mmol=l (males) and 100 mmol=l (females), and for plasma urea it is 7.6 mmol=l (males) and 6.8 mmol=l (females).…”
Section: Discussionmentioning
confidence: 97%
“…Functional B 12 deficiency in North America has also been highlighted (Pennypacker et al, 1992;Lindenbaum et al, 1994;Carmel et al, 1999;Stabler et al, 1999), especially in Caucasians (Carmel et al, 1999;Stabler et al, 1999). It is unlikely to be due to a simple lack of vitamin B 12 in the diet, and thus is more likely to relate to impaired absorption or retention of the vitamin, by mechanisms that remain poorly understood (Howard et al, 1998;van Asselt et al 1998). A recent study has demonstrated a correlation between severity depression and MMA, but not serum vitamin B 12 in older American women (Penninx et al, 2000), thus raising the possibility of subtle functional (neurological) effects of early vitamin B 12 deficiency.…”
Section: Discussionmentioning
confidence: 99%